Hubungan Antara Kecerdasan Emosional Dengan Hasil Belajar Seni Musik Kelas XI SMA Negeri 1 Ujungbatu - Aidha Thania; Tulus Handra Kadir (SENDRATASIK UNP, 2019)
This article aimed to determine the relationship between emotional intelligence and Music Art Learning Outcomes of the class IX in Senior High School 1 Ujungbatu. Type of research was quantitative research. The forms of research instrument were questionnaires and documentation. The types of data in this study were both primary and secondary. Techniques of data collection were done by giving questionnaire and documentation. Data analysis was done in several stages, namely test requirements analysis and hypothesis testing. Based on the results of the study, the contribution coefficient between emotional intelligence and learning outcomes is obtained at 23.74%. From the data analysis test, it is found that the data is normal and homogeneous. The test result is at the significance level of α 0.05 (95% of confidence level) obtained a value of rcount = 0.4878 and rtable = 0.220 so that it is obtained rcount> rtable (0.4878> 0.220). This is reinforced by the results of the significance test which shows tcount = 4.9351 and ttable = 1.990 so that tcount> ttable (4.9351> 1.990) is obtained. Thus H0 is rejected and H1 is accepted which means that there is a positive and significant relationship between emotional intelligence and the Music Art Learning outcomes of the class XI in Senior High School 1 Ujungbatu.